Learning "betwixt and between": Opportunities and challenges for student-driven partnership - Barrineau, Susanna; Anderson, Lakin (International Journal for Students as Partners, 2018)
This paper analyses students’ experiences of a partnership learning community in which students take on an unusual amount of power over decision-making in the design and implementation of interdisciplinary education. Student-driven contexts are largely absent in literature on partnership in higher education, which has thus far been based on empirical study of institutional contexts in which faculty have more power than students. This reveals a gap in knowledge about arrangements in which students have more control over decision-making than faculty. Drawing from in-depth interviews with student course coordinators, and using the concepts of roles and liminality, we analyse how course coordinators perceive their challenging and often ambiguous roles in which they renegotiate their relationships to staff, students, and the university itself. We then identify some challenges and opportunities for partnership within this context.